2020
DOI: 10.1139/apnm-2019-0501
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor is associated with human muscle satellite cell differentiation in response to muscle-damaging exercise

Abstract: Muscle satellite cell (SC) regulation is a complex process involving many key signalling molecules. Recently, the neurotrophin brain-derived neurotropic factor (BDNF) has implicated in SC regulation in animals. To date, little is known regarding the role of BDNF in human SC function in vivo. Twenty-nine males (age, 21 ± 0.5 years) participated in the study. Muscle biopsies from the thigh were obtained prior to a bout of 300 maximal eccentric contractions (Pre), and at 6 h, 24 h, 72 h, and 96 h postexercise. BD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…In line with these rodent studies, the bed-rest-induced increase in BDNF in old, but not young people, was suggested to be a neuroprotective response [29,30]. In addition to neuroprotection, the concomitant increase in circulating BDNF after muscle-damaging exercise and satellite cell activation [31] suggests that BDNF also facilitates muscle recovery from damage. Although no significant change in BDNF has been observed in young participants after 14 days of bed rest [29,30], it is possible that bed-rest-induced decrements in BDNF occur later in younger than older people and can be prevented by human centrifugation.…”
Section: Introductionmentioning
confidence: 67%
“…In line with these rodent studies, the bed-rest-induced increase in BDNF in old, but not young people, was suggested to be a neuroprotective response [29,30]. In addition to neuroprotection, the concomitant increase in circulating BDNF after muscle-damaging exercise and satellite cell activation [31] suggests that BDNF also facilitates muscle recovery from damage. Although no significant change in BDNF has been observed in young participants after 14 days of bed rest [29,30], it is possible that bed-rest-induced decrements in BDNF occur later in younger than older people and can be prevented by human centrifugation.…”
Section: Introductionmentioning
confidence: 67%
“…Although these studies have been carried out with animals, these data correlate well with human muscle physiology (25,39).…”
Section: Discussionmentioning
confidence: 73%
“…BDNF also has important influence on other tissues. It is engaged in the endogenous reparation of myocardial and skeletal muscle cells [ 89 , 90 ]. BDNF activity is also negatively correlated with insulin resistance, obesity and blood glucose levels [ 91 , 92 ].…”
Section: Myokinesmentioning
confidence: 99%